On the phytoplankton bloom in coastal waters of southern King George Island (Antarctica) in January 2010: An exceptional feature? - Schloss, Irene Ruth; Wasilowska, A; Dumont, D; Almandoz, Gaston Osvaldo; Hernando, Marcelo Pablo; Michaud Tremblay, C. A; Saravia, L.; Rzepecki, M.; Monien, P.; Monien, D.; Kopczynska, E. E.; Bers, A.V.; et al. (Limnology and Oceanography)
Since the early 1990s, phytoplankton has been studied and monitored in Potter Cove (PC) and Admiralty Bay (AB), King George/25 de Mayo Island (KGI), South Shetlands. Phytoplankton biomass is typically low compared to other Antarctic shelf environments, with average spring—summer values below 1 mg chlorophyll a (Chl a) m−3. The physical conditions in the area (reduced irradiance induced by particles originated from the land, intense winds) limit the coastal productivity at KGI, as a result of shallow Sverdrup's critical depths (Zc) and large turbulent mixing depths (Zt). In January 2010 a large phytoplankton bloom with a maximum of around 20 mg Chl a m−3, and monthly averages of 4 (PC) and 6 (AB) mg Chl a m−3, was observed in the area, making it by far the largest recorded bloom over the last 20 yr. Dominant phytoplankton species were the typical bloom-forming diatoms that are usually found in the western Antarctic Peninsula area. Anomalously cold air temperature and dominant winds from the eastern sector seem to explain adequate light : mixing environment. Local physical conditions were analyzed by means of the relationship between Zc and Zt, and conditions were found adequate for allowing phytoplankton development. However, a multiyear analysis indicates that these conditions may be necessary but not sufficient to guarantee phytoplankton accumulation. The relation between maximum Chl a values and air temperature suggests that bottom-up control would render such large blooms even less frequent in KGI under the warmer climate expected in the area during the second half of the present century. Fil: Schloss, Irene Ruth. Ministerio de Relaciones Exteriores, Comercio Interno y Culto. Dirección Nacional del Antártico. Instituto Antártico Argentino; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Université du Québec à Rimousk; Canadá Fil: Wasilowska, A. Warsaw University; Polonia Fil: Dumont, D. Université du Québec à Rimousk; Canadá Fil: Almandoz, Gaston Osvaldo. Universidad ...